Report on the City-to-City-Learning Programme: the replication strategy in Replicate EU-H2020-Smart Cities and Communities (SCC) Lighthouse Project - Calzada, I (University of Oxford, 2019)
The REPLICATE EU Lighthouse project (#ReplicateEU) has been working on its Replication main activity entitled ‘City-to-CityLearning Programme 2019′ (#City2CityLearning) led by the University of Oxford (Dr Igor Calzada, PI) with the participation of the Lighthouse (San Sebastián, Florence, and Bristol) and follower/fellow (Essen, Lausanne, and Nilüfer) cities and their related multitaskholder framework that would take place during the whole year of 2019.